Serial block‐face scanning electron microscopy reveals novel intercellular connections in human term placental microvasculature. Issue 2 (3rd April 2020) - Palaiologou, Eleni; Goggin, Patricia; Chatelet, David S.; Ribeiro de Souza, Rodolfo; Chiu, Wendy; Ashley, Brogan; Lofthouse, Emma M.; Sengers, Bram G.; Torrens, Christopher; Page, Anton M.; Cleal, Jane K.; Lewis, Rohan M.
Abstract: The placental microvasculature is a conduit for fetal blood allowing solute exchange between the mother and the fetus. Serial block‐face scanning electron microscopy (SBF SEM) allows ultrastructure to be viewed in three dimensions and provides a new perspective on placental anatomy. This study used SBF SEM to study endothelial cells within the human placental microvasculature from uncomplicated pregnancies. Term human placental villi were aldehyde‐fixed and processed for imaging by SBF SEM. Manual segmentation was carried out on a terminal villous capillary and an intermediate villous arteriole and venule. Twenty‐seven SBF SEM stacks from terminal villi were analysed using stereological approaches to determine the volumes of microvascular components and the proportions of pericyte coverage. SBF SEM analysis of capillary endothelial cells revealed the presence of interendothelial protrusions (IEPs) originating from the donor cell at the endothelial junction and forming deep thin projections up to 7 μm into the adjacent endothelial cells. IEP density was estimated to be in the order of 35 million cm –3 placental tissue. Pericytes cover 15% of the fetal capillary surface area in terminal villi. In comparison, the cytotrophoblast covered 24% of the syncytiotrophoblast basal membrane. A trans‐endothelial channel was observed in a region of the vasculo‐syncytial capillary. Pericyte coverage was extensive in both arteriole and venule. Three‐dimensional imaging of the placental microvasculature identified novel ultrastructural features and provided an insight into factors that may influence capillary permeability and placental function. We hypothesise that the IEPs may allow mechanosensing between adjacent endothelial cells to assist in the maintenance of vessel integrity. The numbers of endothelial junctions, the presence of trans‐endothelial channels and the extent of pericyte coverage all provide an insight into the factors determining capillary permeability. Abstract : Serial block‐face scanning electron microscopy to create a 3D reconstruction of endothelial cells. Interendothelial protrusions were observed originating from a donor endothelial cell and tunnelling inside a recipient endothelial cell. These structures constitute a novel intercellular connection.